The Effect of Methylmetacryalte Exposure on The Incidence of Asthma Bronchiale - Muchammad Arief Gunawan; Indah suci Widyahening; Muhammad Ilyas (ILUNI MKK FKUI and PRODI MKK FKUI, 2023)
Background: Asthma is one of the major health problems in the world. An estimated 300 million people worldwide suffer from asthma, with 250.000 deaths each year from asthma. The prevalence of asthma has continued to increase in recent years, Asthma affects 1 in 14 people in America in 2001 while in 2009 the rationale was 1 patient in 12 people The aim of this report is to get a systematically searching in order to get an answer about the risk factor of the Asthma bronchiale and the prevention measure.Methods: A 40-year-old woman who works as a dental technician complains of experiencing symptoms of shortness of breath, wheezing, coughing and cold. A search was carried out to obtain clinical answers with databases obtained from: PubMed, and ProQuest. With the keyword “Worker”, “Methyl Methacrylate OR Acrylic” AND “Occupational Asthma” with inclusion criteria cohort studies, case control studies, cross sectional studies, methyl methacrylate, occupational asthma, occupational, and case report. Results: One study was found that there was a relationship between asthma and exposure to methacrylate. Risk of doctor-diagnosed asthma within 12 months (OR 27.6, 95% CI 1.19 - 7-54) and adult-onset asthma (2.65, 1.14-7.24) when compared with those not exposed to methyl methacrylate.Conclusion: From the two studies that we have been reviewed there was a significant relationship between exposure of methyl methacrylate or acrylic to the incidence of asthma.